The Importance of Initial Evaluation by Trans Vaginal Sonography in Rudimentary Horn Pregnancy: A Case Report and Literature Review - Asgari Zahra; Razavi Maryam; Hoseini Rayhaneh; Rezaeinejad Mahroo; Rooholamin Safora; Javaheri Atieh; Ahmadi Farahnazsadat (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Rudimentary  horn  pregnancy  (RHP)  as  a  rare  incidence  has  been  estimated  at  1:76,000- 1:150,000 pregnancies. It has been also reported that 80-90% of RHP lead to uterine rupture in second trimester.  Early  diagnosis  with  the  use  of  3-dimentional  ultrasonography  (3-DUS)  that  is  followed by  laparoscopic  resection  of  RH  and  ipsilateral  fallopian  tube  is  likely  to  be  considered  as  the  best management strategy that prevents maternal morbidity and mortality. We present a case of 9-week pregnancy  in  a  non-communicating  rudimentary  horn  with  positive  fetal  heart  rate  (FHR)  that  was diagnosed by 3-DUS and successfully treated with laparoscopic resection.